2015
DOI: 10.1088/0004-637x/800/2/95
|View full text |Cite
|
Sign up to set email alerts
|

KEPLERFLARES III: STELLAR ACTIVITY ON GJ 1245A AND B

Abstract: We present the flare occurrence rates and starspot evolution for GJ 1245 A and B, two active M5 stars, based on nine months of Kepler short cadence observations, and four years of nearly continuous long cadence observations. The A component is separated from the B component by 7 , and the stars are not resolved in the Kepler pipeline processing due to Kepler's large plate scale of 4 /pixel. Analyzing the target pixel data, we have generated separate light curves for components A and B using the PyKE pixel resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 30 publications
14
80
0
Order By: Relevance
“…Recent studies on optical flares done with ground-based observatories on DV Psc (Pi et al, 2014) and CU Cnc (Qian et al, 2012) show flare frequency of ∼2 flares per day and ∼1 flare per day, respectively, which is similar to that for LO Peg. However, several other studies done with Kepler satellite (Hawley et al, 2014;Lurie et al, 2015) on M dwarfs reveal that flare frequency varies over a wide range of ∼1 flare per month to ∼10 flares per day. In our study, we have also detected an X-ray flare simultaneously observed with the UV-band.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies on optical flares done with ground-based observatories on DV Psc (Pi et al, 2014) and CU Cnc (Qian et al, 2012) show flare frequency of ∼2 flares per day and ∼1 flare per day, respectively, which is similar to that for LO Peg. However, several other studies done with Kepler satellite (Hawley et al, 2014;Lurie et al, 2015) on M dwarfs reveal that flare frequency varies over a wide range of ∼1 flare per month to ∼10 flares per day. In our study, we have also detected an X-ray flare simultaneously observed with the UV-band.…”
Section: Discussionmentioning
confidence: 94%
“…The local mean flux (F lm ) and standard deviation (σ ql ) of the flux were then computed at each time-sampled data set. To avoid misdetection of short stellar brightness enhancement as a flare, candidate flares were flagged as excursions of two or more consecutive data points above 2.5σ ql from F lm (see Hawley et al, 2014;Davenport et al, 2014;Lurie et al, 2015) with at least one of those points being 3σ ql above F lm in any of the optical band. Once the flare was detected using the above criteria, the flare segment was removed to calculate the exact value of σ ql , where most of the flares were identified above the 3σ ql from the quiescent state.…”
Section: Flare Analysismentioning
confidence: 99%
“…The largest flares in our sample have log E ∼ 31.5 erg, more than 2 orders of magnitude smaller in energy. However, Lurie et al (2015) found using much longer time-series from Kepler that the FFD for M5 stars can reach energies of at least log E ∼ 33 erg. Extending our FFD fit from Figure 3, we predict Proxima Cen could produce ∼8 flares at log E = 33 erg per year.…”
Section: Flare Statisticsmentioning
confidence: 99%
“…Flare frequency uncertainties were calculated using the Poisson confidence intervals (Gehrels 1986), while errors for the flare energies were computed as the inverse signal to noise ratio (e.g. see Lurie et al 2015). The apparent saturation of the flare rate at low energies is due to incompleteness in recovering low amplitude events.…”
Section: Flare Statisticsmentioning
confidence: 99%
“…Another possibility is a nonlinear response of pixels to increasing incident flux due to saturation. Saturation effects in Kepler data have been encountered and discussed by Lurie et al (2015); Luger et al (2016). Our target star is significantly fainter than the Kp = 11.3 mag which is believed to be the saturation threshold (Gilliland et al 2010).…”
Section: Vim Detectionsmentioning
confidence: 74%